Acute Kidney Injury in Cardiac Surgery Patients: Role of Glomerular Filtration Rate and Fat-Free Mass - Januškevičiūtė, Elija; Vicka, Vaidas; Krauklytė, Justina; Vickienė, Alvita; Ringaitienė, Donata; Šerpytis, Mindaugas; Šipylaitė, Jūratė (Acta medica Lituanica, 2021)
Background: eGFR (estimated glomerular filtration rate) formulas may be inaccurate in overweight cardiac surgery patients, overestimating the kidney reserve. The aim of this study was to modify the eGFR formulas and to determine whether the modified eGFR is a more accurate predictor of acute kidney injury (AKI).Materials and methods: The patients were assigned into 4 BMI groups as follows: normal weight (18.5–25 kg/m2), pre-obesity (25–30 kg/m2), class I obese (30–35 kg/m2), class II and III obese (≥35 kg/m2). Cockcroft–Gault (CG) eGFR formula was modified by using the fat-free mass (FFM) derived from bioelectrical impedance. ROC-AUC curves were analyzed to identify the accuracy of the eGFR formulas (CG, CG modified with FFM, Mayo Clinic Quadratic equation, CKD-EPI, MDRD) to predict the AKI in each group.Results: Although all of the used equations showed similar predictive power in the normal weight and overweight category, Mayo formula had the highest AUC in predicting the occurrence of AKI (ROC-AUC 0.717 and 0.624, p
Keywords: acute kidney injury; eGFR; fat-free mass